Integrating Social Media into English Language Learning: A Systematic Literature Review - Dianda Putri (Indonesian Language Education and Applied Linguistics Reviews, 2026)
This paper presents a systematic review of how social media has been integrated into English language learning between 2019 and 2025. The aim is to identify the main benefits, challenges, and best practices reported in recent studies.  A review of pertinent research articles reveals the ways in which educational platforms such as YouTube, Instagram, and TikTok have facilitated the enhancement of vocabulary, motivation, and interaction among learners in both formal and informal educational settings. The review also identifies several challenges, including distractions, privacy concerns, and disparities in device and internet access. Nevertheless, numerous studies have demonstrated that, when utilized in conjunction with adequate guidance, social media has the potential to enhance the engagement and significance of the learning process for English language acquisition. This paper offers a comprehensive overview of the key findings and provides recommendations for teachers, learners, and future researchers to enhance the utilization of social media in language education.